Efecto de diferentes concentraciones del extracto clorofórmico de hojas de Annona muricata L. “guanábana” y tiempos de exposición sobre el índice mitótico de Allium cepa L. “cebolla” var. Arequipeña. - RUIZ BACA, Jesús (2019)
The objective of the present investigation was to determine how the different concentrations and exposure times of the chloroform extract of Annona muricata L. "guanábana" influence the mitotic index of Allium cepa L; for which the rootlets of the bulbs were exposed to five concentrations and four times to the chloroform extract, then they were fixed in carnoy's, then the cytological preparations were obtained, finally the reading was done under a microscope. The results showed that the mitotic index of the treatments exposed to the chloroform extract decreased markedly compared with the control treatments, where the T20 (1.5mg / L-24 hours) evidenced the lowest mitotic index. Therefore the mitotic index of the meristematic cells of Allium cepa L. decreases as it increases the concentrations and times of exposure to the chloroformic extract of Annona muricata L. "guanábana".